Sosialisasi Badan Permusyawaratan Desa Dalam Meningkatkan Demokrasi Lokal - Fakhruri, Hajmi; Marlina, Lina; Aulawi, Anton (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
This community service aims to discover how village deliberative bodies improve local democracy and what obstacles village deliberative bodies have in improving local democracy in Kramatlaban village, sub-district. Padarincang district. attack prov. offer. This community service uses a survey method to the direct location. The subjects of this community service are the chairman of the Kramatlaban village BPD, the Kramatlaban village BPD secretary, the Kramatlaban village head, the Kramatlaban village secretary and the Kramatlaban village community. The results of community service show that the BPD in Kramatlaban Village has carried out its main duties and functions, namely establishing Village Regulations together with the Village Head, accommodating and channeling community aspirations, and supervising the Village Head's performance well. There are 2 (two) obstacles to BPD in carrying out its role, namely internal and external factors. The following are internal factors: (1) Facilities, (2) Financial obstacles, (3) Limited time. Meanwhile, for external factors: (1) Participation from the community is less than optimal. The efforts made by the BPD to improve local democracy are: (1) Providing knowledge to the community about the importance of democracy, (2) Providing any information on village community management reports to the village government, and (3) Carrying out outreach with the community regarding the functions and duties of the BPD.